RBM20 Mutations Induce an Arrhythmogenic Dilated Cardiomyopathy Related to Disturbed Calcium Handling. Issue 13 (25th September 2018) - van den Hoogenhof, Maarten M.G.; Beqqali, Abdelaziz; Amin, Ahmad S.; van der Made, Ingeborg; Aufiero, Simona; Khan, Mohsin A.F.; Schumacher, Cees A.; Jansweijer, Joeri A.; van Spaendonck-Zwarts, Karin Y.; Remme, Carol Ann; Backs, Johannes; Verkerk, Arie O.; et al.
Abstract : Background: Mutations in RBM20 (RNA-binding motif protein 20) cause a clinically aggressive form of dilated cardiomyopathy, with an increased risk of malignant ventricular arrhythmias. RBM20 is a splicing factor that targets multiple pivotal cardiac genes, such as Titin (TTN) and CAMK2D (calcium/calmodulin-dependent kinase II delta). Aberrant TTN splicing is thought to be the main determinant of RBM20-induced dilated cardiomyopathy, but is not likely to explain the increased risk of arrhythmias. Here, we investigated the extent to which RBM20 mutation carriers have an increased risk of arrhythmias and explore the underlying molecular mechanism. Methods: We compared clinical characteristics of RBM20 and TTN mutation carriers and used our previously generated Rbm20 knockout (KO) mice to investigate downstream effects of Rbm20-dependent splicing. Cellular electrophysiology and Ca 2+ measurements were performed on isolated cardiomyocytes from Rbm20 KO mice to determine the intracellular consequences of reduced Rbm20 levels. Results: Sustained ventricular arrhythmias were more frequent in human RBM20 mutation carriers than in TTN mutation carriers (44% versus 5%, respectively, P =0.006). Splicing events that affected Ca 2+ - and ion-handling genes were enriched in Rbm20 KO mice, most notably in the genes CamkIIδ and RyR2. Aberrant splicing of CamkIIδ in Rbm20 KO mice resulted in a remarkable shift of CamkIIδ toward the δ-A isoform that is known to activate the L-type Ca 2+ current ( I Ca, L ). In line with this, we found an increased I Ca, L, intracellular Ca 2+ overload and increased sarcoplasmic reticulum Ca 2+ content in Rbm20 KO myocytes. In addition, not only complete loss of Rbm20, but also heterozygous loss of Rbm20 increased spontaneous sarcoplasmic reticulum Ca 2+ releases, which could be attenuated by treatment with the I Ca, L antagonist verapamil. Conclusions: We show that loss of Rbm20 disturbs Ca 2+ handling and leads to more proarrhythmic Ca 2+ releases from the sarcoplasmic reticulum. Patients that carry a pathogenic RBM20 mutation have more ventricular arrhythmias despite a similar left ventricular function, in comparison with patients with a TTN mutation. Our experimental data suggest that RBM20 mutation carriers may benefit from treatment with an I Ca, L blocker to reduce their arrhythmia burden. Abstract : Supplemental Digital Content is available in the text.